(untitled) (Indian Journal of Chemistry (IJC), 2024)
Benzimidazole and Benzothiazole based two compounds are studied whether those can bind with poly-A.poly-T DNA sequence or not and their mode of binding also explored. According to thermal denaturation data, BNTZA slightly favors DNA stability with a 2.9 °C advantage over BNIMZ. The DNA conformational stability of the B-DNA form was recorded with and without ligands by circular dichroism. The estimated docking scores support the findings from the UV denaturation investigation, and we observed that BNTZA had a higher docking score than BNIMZ. With the help of 50 ns MD simulations additional conformational analysis was verified. Both compounds effectively bind to the minor-grooves of AT-rich DNA sequence with a favorable binding free energy in accordance with the RMSD analysis, and pucker distribution of deoxyribose sugars. Future oligonucleotide therapies may be benefited because of the current discovery.